Pengaruh Latihan Gerak Aktif Kaki dengan Teknik Open Kinetic Chain Exercise terhadap Penurunan Intensitas Nyeri pada Lansia dengan Nyeri Sendi Osteoartritis dan Rheumatoid - Prio, Asminarsih Zainal; Misbah, Sitti Rachmi; Wijayati, Fitri (Health Information : Jurnal Penelitian, 2017)
There was not specialy exercise for elderly with pain caused by osteoarthritis and rheumatoid at the Minaula Social Institution of Elderly at Kendari. This researches aims to examine the effect of foot exercise with open kinetic chain methods on decreasing pain on elderly with pain caused by osteoarthritis and rheumatoid at the Minaula Social Institution of Elderly at Kendari. The method used in this research was quasi experimental using pretest and posttest with control group design. Data collections was conducted by simple random sampling to reach 60 participant 930 in intervention group and 30 in control group). The result showed that mean of pain level of intervention group was decreased as 4,83 after foot exercise with open kinetic chain methods (mean before 5,80, mean after 0,97). The conclution of this research there was an effectiveness of foot exercise with open kinetic chain methods to decreased pain level in elderly with pain caused by osteoarthritis and rheumatoid at Minaula Social Institution of Elderly at Kendari 2016 (p value = 0,000). This research implied that foot exercise with open kinetic chain methods can be consider as one of nursing competencies and applied as a nursing intervention to decreased pain level caused by osteoarthritis and rheumatoid.